Business process management : 17th international conference, BPM 2019, Vienna, Austria, September 1-6, 2019, proceedings /: 17th international conference, BPM 2019, Vienna, Austria, September 1-6, 2019, proceedings. ([2019]) - Unknown
No abstract available